Assessment of Cleaning Methods for Solar PV Modules: A Review of Current Practices - Aditya Dhamale; Tejaswi Jamankar Jamankar; Omkar Kshirsagar; Sujit S. Jalkote (International Journal of Electrical Machine Analysis and Design, 2024)
This study looks at how well solar panel cleaning technologies work to increase energy output, lower maintenance costs, and lengthen the life of solar panel systems. The necessity for efficient and economical maintenance of solar panels is growing in importance due to the rising demand for solar energy. Systems for cleaning solar panels have become a viable way to address the problem of maintaining clean and efficient solar panels. Our study encompasses an extensive examination of previous research on automated solar panel cleaning systems in the literature, in addition to a data analysis of field testing and experiments. We look at the technology underlying these systems, how well they work in different settings, and how they affect society and the environment. According to our research, solar panel cleaning devices can increase energy output while lowering maintenance expenses. These technologies can also increase the longevity of solar panel systems, which increases their long-term sustainability. More research is necessary to fully understand the environmental and economic effects of implementing these systems on a bigger scale.
Keywords: Solar Panel; anisotropic ratchet conveyors; automated system; cleaning; portable PV cleaning robot system